2013
DOI: 10.1007/s11604-013-0237-1
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MRI of renal cell carcinoma, upper tract urothelial carcinoma, and renal infection: a pictorial review

Abstract: Diffusion-weighted (DW) magnetic resonance imaging (MRI) is a functional imaging technique that derives image contrast from differences in water molecule diffusion within tissues. DW MRI helps detect and characterize renal and urothelial malignancies, may help in differentiating some benign from malignant renal masses, and can also recognize renal and upper urinary tract infections. Patients precluded from receiving intravenous contrast agents may particularly benefit from this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For those who are not suitable for CT urography, similar MR imaging protocols exist [46]. Investigators have found that by adding diffusion-weighted imaging, the accuracy and sensitivity for detecting UTUC at MRI can be significantly improved, and this may be a useful adjunct in preoperative assessments of tumor grade or aggressiveness [47]. PET/CT scans have been found to be highly sensitive for primary and metastatic bladder and upper tract TCC [48,49].…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…For those who are not suitable for CT urography, similar MR imaging protocols exist [46]. Investigators have found that by adding diffusion-weighted imaging, the accuracy and sensitivity for detecting UTUC at MRI can be significantly improved, and this may be a useful adjunct in preoperative assessments of tumor grade or aggressiveness [47]. PET/CT scans have been found to be highly sensitive for primary and metastatic bladder and upper tract TCC [48,49].…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…There may be resultant hydronephrosis depending on the location of the tumor [ 30 ]. On MRI, the tumor may appear isointense to slightly hypointense on T1 weighted imaging, isointense to mildly hyperintense on T2 weighted imaging, with mild, heterogenous enhancement post-contrast [ 31 ].
Fig.
…”
Section: Malignant Mimicsmentioning
confidence: 99%
“…Although diffusion restriction is most commonly associated with solid lesions, it can also occur with acute, subacute or chronic infection. A renal abscess could simulate a solid renal mass on DWI/ADC due to marked diffusion restriction owing to the viscous fluid containing bacteria, mucoid proteins and cellular debris . Infection can however be potentially differentiated from tumour in that there is a discrepancy between the amount of diffusion restriction and the lesser amount of enhancement that is seen on the post‐contrast sequences, as illustrated in the case described above.…”
mentioning
confidence: 99%